Fade & cut barber / Muhammad Harith Zainul Asri ...[et al.] - Zainul Asri, Muhammad Harith; Ahmad Shukri, Raja Imran Hakimi; Mohd Nor, Muhamad Daniel Hakim; M Ghazali, Irfan Aqil; Hairul Nizam, Muhammad Asyraf (2022)
Fade & Cut Barber (FCB) is a partnership business consisting of five members. Each of the members hold essential positions in the business, which are General Manager, Administrative Manager, Marketing Manager, Operational Manager, and Financial Manager. Each positions have their respective roles and responsibilities in the business, and the qualities of their work plays a huge role in determining the progress and success of the business. The mission of this company is to provide an affordable hair related services and products that are high quality and worthwhile. A dominant and competitive barbershop is the image that we imagine ourselves to be in the future and as such, ensuring only top quality services and and products are delivered to our customers, will always be the main focus of the company as we move forward. The vision of the company is to become the largest and most well-known barbershop in Pasir Gudang by providing an incomparable quality of service and highest level of satisfaction to our customers.